The Effect of E-Service Quality and E-Trust on E-Customer Loyalty Through E-Satisfaction as an Intervening Variable Among Tiktok Shop Users in Denpasar City - Made Tarita Kezaravijaya Yuana; Ni Luh Putu Indiani; Ida Ayu Surasmi (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to analyze the influence of e-service quality and e-trust on e-customer loyalty, with e-satisfaction as a mediating variable among TikTok Shop users in Denpasar City. This research is motivated by the rapid development of e-commerce, which intensifies competition among digital platforms. As a result, companies are required not only to attract new customers but also to maintain customer loyalty by improving electronic service quality and building consumer trust. The study is theoretically based on the Theory of Planned Behavior (TPB), which explains that individual behavior is influenced by attitudes, subjective norms, and perceived behavioral control that shape the intention to perform a particular action. This study employs a quantitative approach using purposive sampling with 100 respondents who are TikTok Shop users in Denpasar City. Data were collected through questionnaires and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results show that e-service quality and e-trust have a positive and significant effect on e-satisfaction and e-customer loyalty. Furthermore, e-satisfaction also has a positive and significant effect on e-customer loyalty and is proven to act as a partial mediating variable in the relationship between e-service quality and e-trust on e-customer loyalty. These findings indicate that improving digital service quality and consumer trust can enhance customer satisfaction, which ultimately strengthens customer loyalty in e-commerce platforms.